Evaluation of the Community Approach and The Resurgence of Malaria Cases in the Province of Maniema and Kwango in the Democratic Republic of Congo - Mwabi, Priss Tambwe; Bonny, Assani Wakenge; Alphonse, Masandi Milondo; John, Kahozi Mihali; Désiré, Kibonge Pascal; Jeanne d’Arc, Iragi Mundinga; Placide, Mbungi Pangalala (British Journal of Healthcare and Medical Research, 2024)
This study evaluated the community-based approach and the resurgence of malaria cases. It covered two provinces of the Democratic Republic of Congo, including Maniema and Kwango, and was a case-control study based on a retrospective interview of two people hospitalised (or on sick leave) for severe malaria between 2021 and 2022, with a sample size of 800 households. The population of households surveyed had knowledge of the danger signs of malaria (95.4%), the causal agent and the cause of mosquito development. To combat the resurgence of cases of malaria, this population protects itself by using insecticide-impregnated bed nets and by weeding the environment and evacuating breeding grounds